Penjadualan Produksi Flowshop dengan Availability Constraints Genetic Algorithm dan Tabu Search untuk Minimalisasi Makespan Time - Wawan Indarto (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2004)
This work describes a genetic algorithm and tabu search approach that will behybrided to CDS algorithm to solve the flowshop scheduling with availability constraint. Insuch problem, machine are not available to work with, because it must entering themaintenance time. In this paper, two variant of non preemptive with an arbitrary number ofmachines and arbritary number of unavailability constrainton each of them considered.Computational experiments are performed on randomly generated instances to show theefficiency of the proposed approaches.Keywords: flowshop, multiple objectives, genetic algorithm, availability constraint, tabusearch.